2013
DOI: 10.4025/actasciagron.v35i3.16322
|View full text |Cite
|
Sign up to set email alerts
|

<b>Characterizing zinc use efficiency in varieties of Arabica coffee</b> - doi: 10.4025/actasciagron.v35i3.16322

Abstract: ABSTRACT. Among micronutrients, zinc (Zn) is important for coffee tree cultivation, especially in the clayey acid soils of Brazil's southeast region, where coffee production is an important activity. This study aimed to evaluate the Zn use efficiency of coffee tree varieties using two zinc concentrations. Seedlings of 11 varieties of coffee trees were grown in a greenhouse in nutrient solution containing either 0.0 or 6.0 μmol L -1 of Zn. After eight months, we evaluated the total biomass production, leaf biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
6
0
3
Order By: Relevance
“…Studies with coffee have demonstrated genetic diversity among cultivars for efficiency of absorption, transport and utilization of several nutrients (Amaral et al, 2011a;Amaral et al, 2011b;Pedrosa et al, 2013 andTomaz et al, 2008). However these studies considered the association of macronutrients, especially nitrogen, phosphorus and potassium and/or micronutrients such as boron, copper and zinc, with adequate fertilization, it is then necessary to evaluate the nutritional efficiency for each nutrient separately.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with coffee have demonstrated genetic diversity among cultivars for efficiency of absorption, transport and utilization of several nutrients (Amaral et al, 2011a;Amaral et al, 2011b;Pedrosa et al, 2013 andTomaz et al, 2008). However these studies considered the association of macronutrients, especially nitrogen, phosphorus and potassium and/or micronutrients such as boron, copper and zinc, with adequate fertilization, it is then necessary to evaluate the nutritional efficiency for each nutrient separately.…”
Section: Introductionmentioning
confidence: 99%
“…Nesta dose, as plantas absorveram 0,11 mg de Zn por grama de matéria seca de raízes produzida, possibilitando aumento de 24,5%, quando comparada com a ausência do elemento. Os resultados estão de acordo com os encontrados por Pedrosa et al (2013) em variedades de cafeeiro.…”
Section: Resultsunclassified
“…Araújo et al (2013) A eficiência de utilização do zinco foi reduzida linearmente com a elevação das doses do micronutriente aplicadas ao substrato (Figura 10). Esta redução na eficiência de uso, com o aumento das doses, foi verificada, também, em variedades de cafeeiro (Reis Junior & Martinez, 2002;Pedrosa et al, 2013) e em plantas de arroz (Fageria et al, 2011). Tal fato ocorre porque, nessa condição, a produção de biomassa pelas plantas não sofre incremento na mesma proporção que a absorção e o acúmulo do nutriente nos tecidos ocorrendo, neste caso, declínio na utilização interna do nutriente para a produção de biomassa (Siddiqi & Glass, 1981).…”
Section: Resultsunclassified
“…Recently, similar experiments were developed with the aim of investigating the efficiency use of zinc for coffee genotypes ( The other varieties were moderately efficient in the use of the element (Pedrosa et al, 2013). Among the macronutrients required the absence of nitrogen is the most limiting to the development of the coffee plants; for implication in expanding leaf area and growth of vegetation.…”
Section: Systematic Analysis Of the Nutritional Efficiency Of Coffea mentioning
confidence: 99%